“Vou buscar ali, ali acima!” : A multimodalidade da deixis no português europeu - Isabel Galhano-Rodrigues (Linguística, 2012)
Based on a case study, this article explores multimodal deixis – the ensemble gesture-speech deixis - in European Portuguese. Various forms of pointing gestures will be identified and correlated to simultaneous speech, giving account of the different types of deixis and of the kind of reference established by deictic elements. In the description of the modalities which assume the function of “pointing at”, the following co-textual and contextual aspects were considered: the relevance of indicating an object, a place, a space, a person or an abstract idea; the need for precision in pointing; speakers’ expectations regarding hearers’ knowledge about the referents.